Obispo, comunidad y organización social: el caso de la ‘Vita Emiliani’ - López Campuzano, Manuel (Antigüedad y Cristianismo, 1990)
This article analyses how the function of a Christian cultural center, concretely that of Aemilianus, acted as a factor of social aglutination using the social function of redistribution in areas where the native pagan communities were still latent and contributing in this way to an aculturation process versus conversion.